Program Pendidikan dan Pelatihan Keselamatan dan Kesehatan Kerja (K3) Komprehensif Menuju Budaya Zero Accident dan Zero Risk Bagi Pekerja Konstruksi di Pesanggrahan, Jakarta Selatan - Chairani, Aulia Nasywa; Nabila, Anna; Mazaya, Hasna; Saharawati, Regita; Az-Zahr, Syahla Alifia; Hanifa, Isnaini; Tasya, Naswa; Anjani, Agustin Ratna; Cahyani, Salma Nisrina; Syavira, Ainur Rizqi; Febriani, Nelly (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The high incidence of work accidents globally and nationally, with an increasing trend of 5–7% in Indonesia, was driven by weaknesses in Hazard Identification, Risk Assessment, and Risk Control (HIRARC), low adherence to Safe Work Standard Operating Procedures (SOPs), and insufficient use of Personal Protective Equipment (PPE) among project workers, most of whom had not attended formal Occupational Health and Safety (OHS/K3) training. Therefore, the objective of this activity was to increase the understanding and awareness of construction project workers in Pesanggrahan, South Jakarta, regarding occupational risks through the implementation of a Zero Accident, Zero Risk culture. The method used was interactive lectures and Q&A sessions, supported by media such as PowerPoint, leaflets, and first aid kits, which focused on the topics of HIRARC, First Aid (P3K), near miss reporting, and PPE usage. Through this intervention, an increase in workers’ ability to recognize potential hazards and implement safe procedures was achieved, resulting in the expected outcome of a reduction in accident rates and the realization of a safe, healthy, and productive work environment. The main recommendations emphasized the strengthening of a near miss reporting culture as an early warning system and strict supervision by management to ensure consistent adherence to SOPs and proper PPE use.